THE INTERSECTION BETWEEN FAITH AND HORROR: THE VAMPIRIC ANGELS OF NETFLIX’S MIDNIGHT MASS - Kamilia Kusumadinata (HISKI, 2021)
When it comes to on-screen depictions, oftentimes religion and horror are placed at opposing sides. Religion in film is the antithesis of horror, rarely does it venture into the concept of religion itself as the source. Netflix's Midnight Mass (2021) by Mike Flanagan explores this topic in a deeper yet subtle manner. Since the series was released less than two years before this article was written, most of the articles found are focused on the cinematic aspect and the performance of actors. This article examines the use of overt religiousness to push forward the horror narrative, particularly the interchangeable nature of angels and vampires. By using textual analysis as a method, the writer concludes that horror can only be recontextualized into a holy perspective because religion is the origin of said horror.AbstrakDalam perfilman, agama dan horor seringkali di tempatkan di sisi yang berlawanan. Agama dalam film merupakan antitesis dari horor, terdapat sedikit film horor yang menggunakan konsep agama sebagai sumber dari teror. Acara Netflix Midnight Mass (2021) oleh Mike Flanagan mengeksplorasi topik ini dengan cara yang lebih dalam namun halus. karena acara tersebut dirilis kurang dari dua tahun sebelum naskah ini ditulis, sebagian besar naskah yang ditemukan berfokus pada aspek sinematik dan penampilan para aktor. Jurnal ini mengkaji penggunaan religiusitas yang terang-terangan untuk mendorong narasi horor, khususnya karakteristik-karakteristik malaikat dan vampir yang dapat disamakan. Dengan menggunakan metode analisis tekstual, penulis menyimpulkan bahwa horor hanya dapat di kontekstualisasi ulang menjadi perspektif suci karena agama itu sendiri yang menjadi sumber horor tersebut.